Grandparental immune priming in the pipefish Syngnathus typhle. Issue 1 (December 2017) - Beemelmanns, Anne; Roth, Olivia
Abstract Background Phenotypic changes in response to environmental influences can persist from one generation into the next. In many systems parental parasite experience influences offspring immune responses, known as transgenerational immune priming (TGIP). TGIP in vertebrates is mainly maternal and short-term, supporting the adaptive immune system of the offspring during its maturation. However, if fathers and offspring have a close physical connection, evolution of additional paternal immune priming can be adaptive. Biparental TGIP may result in maximized immunological protection. Here, we investigate multigenerational biparental TGIP in the sex-role reversed pipefishSyngnathus typhle by exposing grandparents to an immune challenge with heat-killed bacteria and assessing gene expression (44 target genes) of the F2-generation. Results Grandparental immune challenge induced gene expression of immune genes in one-week-old grandoffspring. Similarly, genes mediating epigenetic regulation including DNA-methylation and histone modifications were involved in grandparental immune priming. While grand-maternal impact was strong on genes of the complement component system, grand-paternal exposure changed expression patterns of genes mediating innate immune defense. Conclusion In a system with male pregnancy, grandparents influenced the immune system of their grandoffspring in a sex-specific manner, demonstrating multigenerational biparental TGIP. The involvement of epigenetic effects suggests that TGIP via the paternal line may not be limited to the pipefish system that displays male pregnancy. While the benefits and costs of grandparental TGIP depend on the temporal heterogeneity of environmental conditions, multigenerational TGIP may affect host-parasite coevolution by dampening the amplitude of Red Queen Dynamics.